2014
DOI: 10.1166/jnn.2014.8637
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Cyclohexane Using Ce1−xMnxO2 Nanocatalysts

Abstract: The Ce1-xMnxO2 nanocatalysts (x = 0.25, 0.50 and 0.75 wt.%) were synthesized by sol-gel method. The catalysts were characterized using various techniques such as XRD, N2 sorption study, DRSUV-Vis, TPR, SEM and TEM. The incorporation of Mn ions into the ceria lattice was confirmed by XRD analysis. DRUV-Vis spectra confirm the presence of Ce3+ ions in the lattice of Ce1-xMnxO2. H2-TPR study revealed the oxygen storage capacity of the catalyst. The 3D flowerlike morphology of the nanocatalysts was confirmed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The manganese ions incorporated nanocubes (Ce 1-x Mn x O 2 ) are synthesized by precipitation method using urea as follows [37,38] A c c e p t e d M a n u s c r i p t 5 procedure reported earlier [31,36]. Further, MnO 2 catalyst is also synthesized by the same procedure using manganese acetate as the precursor.…”
Section: Preparation Of Ce 1-x Mn X O 2 Nanocubesmentioning
confidence: 99%
See 2 more Smart Citations
“…The manganese ions incorporated nanocubes (Ce 1-x Mn x O 2 ) are synthesized by precipitation method using urea as follows [37,38] A c c e p t e d M a n u s c r i p t 5 procedure reported earlier [31,36]. Further, MnO 2 catalyst is also synthesized by the same procedure using manganese acetate as the precursor.…”
Section: Preparation Of Ce 1-x Mn X O 2 Nanocubesmentioning
confidence: 99%
“…However, pure ceria posses low thermal stability, and leads to low oxygen storage capacity. In-order to improve the thermal stability and catalytic behavior of the catalyst, the transition metals are incorporated into ceria lattice [31,32]. In addition to the well-known particle size effect would make it into better catalytic activity [33,34], also the oxygen storage capacity of the catalysts is closely related to its morphology and exposure active planes [35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of cyclohexane oxidation by air over unsupported Mn oxides showed the highest cyclohexane conversion was achieved for calcination at 400ºC, which was attributed to the higher surface Mn 4+ concentration promoting oxygen mobility and increased oxygen adsorption capacity [18]. The use of Mn containing mixed-metal oxides in oxidation reactions has been studied frequently in the literature [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Mixed metals of variable valency increases oxygen vacancies and enhances oxygen ion mobility. Of particular relevance to the present study are the use of nanostructured MnWO 4 in the oxidative dehydrogenation of propane to propene [20], and of MnCeO x solid solutions for cyclohexane selective oxidation [21,22]. MnWO 4 nanorods prepared by hydrothermal synthesis were found to present higher selectivity to propene than bulk Mn oxide, which was attributed to its unique surface structure containing defect-rich MnO x zigzag chains geometrically isolated by W 2 O 8 units.…”
Section: Introductionmentioning
confidence: 99%